Distribution of pesticides in different commonly grown vegetables of Cameron Highlands, Pahang, Malaysia - Munawar, Nusrat; Yang Farina Abdul Aziz,; Yaqoob, Mohammad; Nabi, Abdul; Shah, Syed Munawar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Gas chromatography-electron capture detector (GC-ECD) is used to extract and analyse pesticides in vegetable samples collected from Cameron Highlands, Pahang, Malaysia. The limit of detection (LOD) for all pesticides was in the range of 0.03 to 4.5 ng g-1. Recoveries in cabbage, lettuce, and celery ranged from 61.8%-121%, 60-128% and 60%-114%, respectively. The relative standard deviation (RSD) ranged 0.2-15% in cabbage, 0.5-18% in lettuce and 3-19.8% in celery. Organochlorine pesticides (OCPs) concentrations increased down the valley with dichlorodiphenyldichloroethylene (DDE) having the highest concentration at 233 μg kg-1. Organophosphorus pesticides (OPPs) were found to be dispersed throughout the valley, with the highest concentration of parathion ethyl (133 μg kg-1) whereas the pyrethroid pesticides (PYRs) concentrations were comparatively less. The detection frequency in the wet season was highest (5 < - < 100 μg kg-1) for most pesticides. However, in the dry season the pesticides concentrations were higher, at < 5 μg kg-1. PCA analysis indicated that farmers were using a mixture of pesticides.